CLIMATE CHANGE IN THE TRIÂNGULO MINEIRO REGION – BRAZIL - Sanches, Fabio de Oliveira; Silva, Roberto Valmir da; Ferreira, Ricardo Vicente; Campos, Carlos Alberto Araújo (Revista Brasileira de Climatologia, 2021)
In the summer of 2013/2014 the Brazil’s Southern region dealt with a severe crisis in water supply. Recent studies have shown that the low volume of rainfall was caused by an anomalous atmosphere blocking condition. Would this anomaly be a regional effect caused by climate change? To answer this question this study aims to analyze the pattern of temperature, rainfall and relative humidity in the Triângulo Mineiro region, located at the Middle Eastern part of Brazil. Temperature (maximum, average and minimum), rainfall and relative humidity data for the weather stations of the Uberaba (1961 – 2015) and Capinópolis (1971 – 2015) cities were submitted to a Mann-Kendall statistical test (MK) in order to investigate trends. The results showed significant positive trends in temperature for both stations. Likewise, the MK test identified a significant negative trend in rainfall and relative humidity for the month of October, thereby suggesting a delay in the return of the rainy season (spring/summer). Analysis of covariance (ANCOVA) showed that there is a relationship between the reduction of rainfall and relative humidity, and the increase in temperature. The rainy season delay severely affects the water resources availability, and combined with expansion of crop areas, population growth, and the increase in temperatures, which leads to the increase in evapotranspiration, worsens the water stress in the Triângulo Mineiro region.